Proceedings of the 2018 International Symposium on Social Science and Management Innovation (SSMI 2018) 2019
DOI: 10.2991/ssmi-18.2019.74
|View full text |Cite
|
Sign up to set email alerts
|

Study on Game Model of Soybean Price: A Case Study of China-US Trade War

Abstract: In China's soybean import market, according to the market share of all countries in China's soybean import market over the years, it is judged that China's soybean import market is a typical duopoly market. In this paper, Brazil and the United States are regarded as two monopoly manufacturers in China's soybean imports, and a dynamic decision-making model composed of these two monopoly manufacturers is established. The chaotic characteristics of the system are analyzed by numerical simulation, bifurcation diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The global feed demand is predicted to almost double by 2050 compared to 2000 (Pradhan et al, 2013). This is particularly important in China, given that there is a high dependency on soybean imports (Gale et al, 2019;Wang, 2019;Li et al, 2021b). Forth, CH 4 emissions from ruminants' enteric fermentation were not considered, which is one of the important GHG to exacerbate global warming.…”
Section: Limitations and Perspectives Of The Studymentioning
confidence: 99%
“…The global feed demand is predicted to almost double by 2050 compared to 2000 (Pradhan et al, 2013). This is particularly important in China, given that there is a high dependency on soybean imports (Gale et al, 2019;Wang, 2019;Li et al, 2021b). Forth, CH 4 emissions from ruminants' enteric fermentation were not considered, which is one of the important GHG to exacerbate global warming.…”
Section: Limitations and Perspectives Of The Studymentioning
confidence: 99%
“…Currently, China is a major importer of soybeans from North and South America (Gale et al, 2019;Wang, 2019), and studies have confirmed that limited land and limited water availability make it difficult and economically disadvantageous for China to increase soybean self-sufficiency. He et al (2019) suggested that replacing some of the existing maize crops with soybeans would improve soybean self-sufficiency as well as environmental and sustainability performance.…”
Section: Feed Non-self-sufficiency In Chinamentioning
confidence: 99%